Environmental Performance Versus Economic-financial Performance: Evidence from Italian Firms - Di Pillo, Francesca; Gastaldi, Massimo; Levialdi, Nathan; Miliacca, Michela (International Journal of Energy Economics and Policy, 2017)
The aim of the study is to evaluate the economic-financial performance of a sample of 236 Italian companies in relation to their environmental performance, measured in terms of CO2 emissions normalized by company turnover. In addition to the company’s economic management, the analysis also considers the equity structure and company liquidity, over a period of six years (2008-2013). The analysis involves the creation of four maps of positioning, serving to represent the companies of the sample in relation to their different attitudes: i) green efficiency; ii) operational efficiency; iii) company profitability; iv) financial viability; v) company liquidity. The examination of positioning maps also serves in identifying extreme cases, meaning the totally inefficient and the “virtuous” companies, and for conducting sectoral analyses to evaluate potential relations between company performances and the characteristics of their industrial sector. Keywords: Environment, CO2 emission, Environmental performance, Economic-financial performance. JEL Classifications: L6, Q5, Q50, Q51